A process for producing ferrite nanocrystals - Saion, Elias; Naseri, Mahmoud Goodarz (2011)
The present invention relates to a process for producing magnetic ferrite nanocrystals by using thermal treatment. The process includes the steps of: firstly, diluting capping agent in deionized water to form a polymeric solution, i.e. polyvinyl pyrrolidone (PVP) solution, secondly, metal nitrate precursors including iron nitrate and at least one metal nitrate are added into PVP solution at room temperature and the solution is stirred until becomes homogenous solution, thirdly, the precursors/PVP solution is placed on a Petri dish and heated in an oven at 70-80C for 18-24 hours for drying and crystallization, fourthly, orange solid crystals which are obtained from heating are crushed and ground in a mortar to form powder, and finally the powder are calcined at calcination temperature of 500-650C to decompose PVP and crystallize the ferrite nanocrystals.